Reflections on Child Behavioral-Analytic Therapy and Functional Analytic Psychotherapy with children (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
The literature on child behavior therapy denounces a lack of applied research that guides service delivery. In Functional Analytical Psychotherapy (FAP) applied to children, that statement is observed and it is noted that the proposal has been used as an adjunct technique to Child Behavioral-Analytic Therapy (CBAT) and with little systematization of the procedures. In this sense, it is considered important to better understand the behavioral processes involved in FAP applied to child population. To do so, a first reflection was made through a comparison between CBAT and FAP with children based on the main publications of Brazilian clinical researches. The following categories were created to be analyzed: the role of the therapeutic relationship, type of reinforcement used, how FAP rules are used, therapy’s goal and intervention focus. It was observed that both proposals share elements and procedures, such as the use of arbitrary and natural reinforcement, therapeutic relationship as the instrument of change, the systematic use or not of FAP rules. The importante difference is at the systematization of the use of the five FAP rules in this therapy, something not followed by CBAT.
Keywords: functional analytic psychotherapy; FAP; child behavioral analytic therapy; psychotherapy; clinic